2015
DOI: 10.1002/biot.201500106
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial cellulose composites: Synthetic strategies and multiple applications in bio‐medical and electro‐conductive fields

Abstract: Bacterial cellulose (BC), owing to its pure nature and impressive physicochemical properties, including high mechanical strength, crystallinity, porous fibrous structure, and liquid absorbing capabilities, has emerged as an advanced biomaterial. To match the market demand and economic values, BC has been produced through a number of synthetic routes, leading to slightly different structural features and physical appearance. Chemical nature, porous geometry, and 3D fibrous structure of BC make it an ideal mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(63 citation statements)
references
References 88 publications
0
53
0
1
Order By: Relevance
“…In agitated cultivation, oxygen is continuously mixed into the medium, so the BC is produced with enhanced yield compared with static culture, which contributes to cost reduction (Ul-Islam et al, 2015). The agitated fermentation process may lead to several forms of cellulose, from fibrous suspension to spheres and pellets (Esa et al, 2014), the shape and size depending on the applied rotational speed (Ul-Islam et al, 2015).…”
Section: Agitated Cultivationmentioning
confidence: 99%
See 1 more Smart Citation
“…In agitated cultivation, oxygen is continuously mixed into the medium, so the BC is produced with enhanced yield compared with static culture, which contributes to cost reduction (Ul-Islam et al, 2015). The agitated fermentation process may lead to several forms of cellulose, from fibrous suspension to spheres and pellets (Esa et al, 2014), the shape and size depending on the applied rotational speed (Ul-Islam et al, 2015).…”
Section: Agitated Cultivationmentioning
confidence: 99%
“…An alternative type of fermentation reactor is airlift bioreactor, in which oxygen is continuously transferred from the bottom of the reactor to the culture medium, providing a suitable oxygen supply (Ul-Islam et al, 2015). The process is more energy efficient and involves less shear stress when compared to stirred-tank reactors (Wu and Li, 2015).…”
Section: Agitated Cultivationmentioning
confidence: 99%
“…It is difficult to form spheres with a rotational speed less than 100 rpm; irregular shapes are observed. Moreover, this method allows a low degree of polymerization, crystallinity, and problematic mechanical properties [45][46][47]. Numerous studies have demonstrated that an agitated/shaken culture may be the most appropriate mode for economic production despite the above-mentioned drawbacks [48].…”
Section: Cultivation Modementioning
confidence: 99%
“…Unlike wood‐based cellulose fibers, the BC nanofibers show various unique properties, namely, (i) high degree of polymerization and crystallinity leading to CTE < 20 ppm K −1 , (ii) tensile strengths of 200–300 MPa, and (iii) Young's modulus up to 78 GPa, resulting in a 8‐fold stronger than stainless steel material. The interested readers can find more information about this material and its application in the following review …”
Section: Ileds Oleds and Lecs Based On Biological Materialsmentioning
confidence: 99%